Mechanism of Center-towards-Surface Enzymatic Hydrolysis Pattern for Sweet Potato Starch Induced by Annealing Treatment and a New Method for Porous Starch Preparation - Yusheng WANG; Hui JIANG; Haihua CHEN (Shipin gongye ke-ji)
Sweet potato and potato starch (which served as a control) were employed as raw materials to explore the characteristics and mechanism of a center-towards-surface enzymatic hydrolysis pattern for sweet potato starch processed at sub-gelatinization temperatures. After being modified by the combination treatment of annealing and α-amylase hydrolysis, the properties of the starch, such as degree of hydrolysis, particle size distributions, thermodynamic properties, microstructures, and crystalline structures, were determined. Results demonstrated that the enzymatic hydrolysis pattern of sweet potato starch after the combination treatment of annealing and hydrolysis was a center-towards-surface pattern, which differed from the surface-towards-center pattern of native starch. The proposed explanation was that the annealing treatment caused the partial swelling of the amorphous region of the sweet potato starch granules. This led to an increase in particle size (with D50 rising by 11.50 μm) and the formation of numerous pores and depressions on the surface. These alterations allowed the enzymes to penetrate into the granule interiors and trigger the hydrolysis, thereby resulting in the development of a hollow shell layer. The combination treatment increased the relative crystallinity of sweet potato starch to 30.9% and the gelatinization peak temperature to 77.7 ℃, without altering the A-type crystalline structure. The results implied that α-amylase was primarily active in the amorphous region. In contrast, potato starch failed to exhibit a center-towards-surface hydrolysis pattern. This difference might be attributed to the long side chains of starch molecules within the B-type crystalline structure of potato starch granules, which formed a stable architecture resistant to enzymatic disruption. Consequently, α-amylase had minimal impact on the amorphous zones of potato starch. After the combination treatment, sweet potato starch's water and oil absorption capacities rose considerably from 2.01 g/g and 3.05 g/g to 3.61 g/g and 3.81 g/g, respectively. This combination treatment of annealing and enzymatic hydrolysis is expected to be a novel approach for the production of porous starch in the food industry.